Method of presentation of expert information by means of fuzzy logic and obtaining the group assessment of expert opinions - Куц, Антон Миколайович (Technology audit and production reserves, 2015)
In the article it is discussed an application of the theory of fuzzy sets to provide expert information, which is not the real linguistic nature. This is particularly relevant for intelligent automated decision support systems, because such systems operate on the basis of expert data. The quality of these systems depends on the chosen method of treatment. To date, there are many methods that allow processing the quantitative expert information as opposed to methods that allow processing the non-numeric data. Since most expert data are expressed in linguistic terms, it should be used the theory of fuzzy sets for their presentation. Therefore, we investigated the possibility of using fuzzy logic and classical methods of expert assessments in this article for presentation and further processing of the results of the expert survey. Adequacy of this approach is shown. Further development of the proposed methods is in their software implementation.